Literatura surda e literatura Coda: produções visuais que retratam realidades culturais singulares - Garcia, Gisele Pereira Gama (2024)
This research is qualitative and addresses the development of Coda Literature. The proposal for this thesis was made, thinking about the self-acceptance and selfidentification of Kodas, that is, hearing children, children of deaf parents, through literary productions. It is known that literature plays a fundamental role in the cultural construction and identity of any person. When researching literary works that portray the lives of these children, few productions were found that only talk about adult children (codas), here in Brazil. This was one of the reasons why the researcher, in addition to proposing Coda Literature, aimed to produce in the country the first book that has Koda characters, talks about these children and is accessible to a diversity of Kodas. The purpose of this thesis is to prove the importance of Coda Literature for Koda children. To reach the objective, bibliographic research was carried out, with the help of several authors, mainly Quadros (2017), Sutton-Spence (2021), (Peixoto 2023), Coelho (2000) and Nascimento (2021) to explain the reactions and importance of literature in the lives of koda children. A survey of literary productions of/for codas or kodas in Brazil and abroad was also carried out to prove their existence and explain the criteria of Coda Literature, proposed in this work. As a research data collection instrument, semi-structured interviews were used with the mothers of the children researched, with the intention of understanding their influence as readers on their children's lives, and participant observation, where the researcher, in addition to observing, makes the considerations. Data collection took place in Juazeiro do Norte/Ce, at Instituto Transformar (INTRA) and was carried out over two days. The methodological procedure unfolded as follows: on the first day, the five selected children came into contact with each other, reading the book individually and interviewing their mothers. On the second day, a reading circle was held—a collective reading of the book. The results were positive, exceeding the researcher's expectations. First, the interviews with mothers impacted this research, showing the urgent need to create and encourage Coda Literature together with mothers, so that they pass on to their children the love of reading from an early age. Many of them do not feel motivated to read with their little ones . Second: during the children's first contact with the book, the kodas, especially the pre-readers in this research, were interested in the story and the details of the book. It was possible to notice, in the analysis, that they recognized many cultural artifacts of deaf people, which are also part of their lives. And in the reading circle, the children, despite being shy, showed that they understood the history and meaning of the word koda, that is, they were made aware of the koda context. In addition to all this, the Coda Literature proposal will bring many benefits to Koda children and adult Codas, the children's father and mother and the deaf community in general. This work can be seen as a door to the literary world of kodas/codas, the beginning of a new area, which will serve as an incentive to the creation of many other literary works, made by kodas/codas or that portray them.